Microdosimetric measurements of shielding effects for iron particles at 500 MeV/nucleon incident upon aluminum and polyethylene - Farrar, David R., author; Borak, Thomas B., advisor; Heilbronn, Lawrence K., committee member; Hulpke, Alexander J., committee member (Colorado State University. Libraries, 2007)
The radiation environment in space is very different than on the earth. One portion of the radiation present in space is galactic cosmic radiation (GCR). GCR is composed of protons, alpha particles, and high Z and energy (HZE) particles. One of the most significant HZE particle species in terms of absorbed dose is iron. One of the dosimetry instruments used on the Space Shuttle and the International Space Station is the tissue equivalent proportional counter (TEPC). It is used to measure absorbed dose and estimate the average quality factor of radiation exposure during manned space missions. TEPCs measure energy deposition in volumes of simulated tissue with dimensions on the order of microns. Spectra of energy depositions are used to calculate values of frequency mean lineal energy, ȳF, and dose mean lineal energy, ȳD. The value of ȳF can be used to calculate the absorbed dose per particle. Previous studies have found that the choice of ȳF or ȳD to approximate particle linear energy transfer (LET), and thus the quality factor, depends on the momentum of the particle and for iron, the value of ȳD is equivalent. However, the presence of material causes HZE particles to slow down and/or fragment. Thus radiation of one HZE particle species incident on one side of shielding material, insufficient to stop all radiation, will produce a wide range of particles and energies on the other side. This study exposed a spherical TEPC, in conjunction with a particle spectrometer, to iron particles at 500 MeV/nucleon, produced at the Heavy Ion Medical Accelerator in Chiba, Japan, with and without shielding material. The shielding material used, in separate measurements, was 1.65 cm Al and 5 cm polyethylene (each has 4.5 g cm-2 density thickness). The density thickness is similar to what is used on the Space Shuttle and International Space Station. The absorbed dose per particle was measured and the average LET of the radiation was estimated for each shielding scenario. For iron particles at 500 MeV/nucleon, the shielding did not cause a change in the absorbed dose per particle. But the shielding reduced the average quality factor of the radiation and polyethylene was better than aluminum, at the same density thickness.
Keywords: Extraterrestrial radiation -- Safety measures; Shielding (Radiation)